2012
DOI: 10.1021/ie202475p
|View full text |Cite
|
Sign up to set email alerts
|

A Max–Min Control Problem Arising in Gradient Elution Chromatography

Abstract: Gradient elution chromatography is an industrial process used to separate and purify multi-component chemical mixtures. In this article, we consider an optimal control problem in which manipulative variables in the chromatographic process need to be determined to maximize separation efficiency. This problem has two nonstandard characteristics: (i) the objective function is nonsmooth, and (ii) each state variable is defined over a different time horizon. The final time for each state variable, the so-called ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…The general switched system framework also encapsulates dynamic systems in which some (or all) of the control variables assume values in a discrete set. Such discrete-valued control variables arise in many applications, including submarine control [11], hybrid power systems [54], micro-robots [4], sensor scheduling [63], switching power amplifiers [57], subway trains [55], and gradient-elution chromatography [12]. An optimal control problem involving discrete-valued control variables is called an optimal discrete-valued control problem [27,68].…”
Section: Introductionmentioning
confidence: 99%
“…The general switched system framework also encapsulates dynamic systems in which some (or all) of the control variables assume values in a discrete set. Such discrete-valued control variables arise in many applications, including submarine control [11], hybrid power systems [54], micro-robots [4], sensor scheduling [63], switching power amplifiers [57], subway trains [55], and gradient-elution chromatography [12]. An optimal control problem involving discrete-valued control variables is called an optimal discrete-valued control problem [27,68].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive numerical testing has shown that the optimal solution obtained is sometimes sensitive to the values chosen for λ and γ. It would be of great benefit to develop a general guide as to the choice of values of these parameters, especially considering the vast array of applications of the exact penalty approach [1,19].…”
Section: Discussionmentioning
confidence: 99%
“…MISER automatically calculates the objective function gradients by integrating a costate system backwards in time; for more details see [1,2,6,11].…”
Section: An Exact Penalty Methodsmentioning
confidence: 99%
See 2 more Smart Citations